Online Games and Security. - McGraw, C. (IEEE Security and privacy : building confidence in a networked world)
Online games have taken the computer world by storm. Gaming has always been (and remains) a prime driver of PC technology, with deep penetration into the consumer market. Online games especially massively multi-player online role-playing games (MMORPGs) suffer from such security problems. In this short introduction to MMORPG security, we focus on bugs involving time and state. MMORPGs are made of very sophisticated software built around a massively distributed client-server architecture.